The "new man" in radical right ideology and practice, 1919-45 - Feldman, Matthew; Dagnino, Jorge; Stocker, Paul (Bloomsbury Academic, 2018)
"An exploration of the ideological attempts by far-right movements across Europe and beyond to create an idealized version of the human race, or a 'new man', during the fascist epoch of 1919 to 1945"--